Shuffled Multiuser Detection Schemes for Uplink Sparse Code Multiple Access Systems - Du, Yang; Dong, Binhong; Chen, Zhi; Fang, Jun; Yang, Lin (IEEE communications letters, 2016)
The existing multiuser detection schemes for uplink (UP) sparse code multiple access (SCMA) systems are based on a parallel message update for message passing algorithm (MPA). In this letter, a shuffled MPA (S-MPA) scheme for UP SCMA systems is proposed, based on a serial message update strategy. Since the updated messages can join the message propagation immediately in current iteration, the convergence rate is accelerated, so that the complexity of the proposed S-MPA scheme can be substantially reduced with negligible bit error rate (BER) degradation. Simulations show that the proposed S-MPA scheme with two iterations provides similar BER performance to the original MPA scheme with six iterations. Furthermore, a parallel form of the proposed S-MPA scheme, termed group S-MPA, is developed to decrease the detection delay of the proposed S-MPA scheme, which offers a good BER-latency tradeoff.